(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
In the article the concept of international economic sanctions is explained; the historical practice of international economic sanctions and effective enforcement criteria are considered; areas, stages, and effects of international economic sanctions against the Russian Federation are defined; prospects of a national economy in the sanctions regime are investigated.